Change in modifiable maternal characteristics and behaviours between consecutive pregnancies and offspring adiposity: A systematic review. (29th May 2020) - Taylor, Elizabeth J.; Wilding, Sam; Ziauddeen, Nida; Godfrey, Keith M.; Berrington, Ann; Alwan, Nisreen A.
Summary: Causal evidence links modifiable maternal exposures during the periconceptional period with offspring obesity. The interconception period may be an important time to intervene. We systematically identified studies examining change in modifiable maternal exposures between pregnancies and offspring adiposity. We searched for longitudinal studies published between 1990 and 2019, which included measurements taken on at least two occasions in the period from 1 year prior to the conception of the first birth to the time of the second birth, and which included a measure of adiposity in second, or higher order, siblings. Age, ethnicity and genetics were not considered modifiable; all other factors including length of the interpregnancy interval were. Eleven studies satisfied the inclusion criteria. Higher interpregnancy weight gain or loss, maternal smoking inception, mothers smoking in their first pregnancy and quitting, increasing the number of cigarettes smoked and longer interpregnancy intervals were positively associated with adiposity in second or higher order children. Vaginal birth after caesarean delivery was protective. Further research is needed to ascertain whether the risk of adiposity is fixed based on first pregnancy exposures or if interpregnancy change alters the risk for a subsequent child. This can inform the type and effectiveness of interventions for mothers prior to a subsequent pregnancy.